Attitudes Toward Arab Ascendance: Israeli and Global Perspectives. (January 2014) - Pratto, Felicia; Saguy, Tamar; Stewart, Andrew L.; Morselli, Davide; Foels, Rob; Aiello, Antonio; Aranda, María; Cidam, Atilla; Chryssochoou, Xenia; Durrheim, Kevin; Eicher, Veronique; Licata, Laurent; et al.
Arab nations are decades behind many other previously colonized nations in developing stronger economies, more democratic institutions, and more autonomy and self-government, in part as a result of external interference. The year 2011 brought the potential for greater Arab autonomy through popular uprisings against autocratic governments in Tunisia, Egypt, and Yemen, and through the Palestinian request for state recognition by the United Nations. We examined the psychology of support for Arab ascendancy among adults in 14 nations in the Balkans, the Middle East, Asia, Oceania, Europe, and North America. We predicted and found that people low on social dominance orientation endorsed forming an independent Palestinian state and desired that the Arab uprisings succeed. Rejection of ideologies that legitimize outside interference with Arabs mediated this support. Measures and model results were robust across world regions. We discuss theoretical implications regarding the advent of new ideologies and extending social dominance theory to address international relations.